UNCOVERING COCOPEAT EXPORT POTENTIAL TO G-20 COUNTRIES: CAN GRAVITY MODELS PROVIDE ANSWERS? - Gunawan, Feryanto; Manullang, Rizal Ruben; Mulyani, Hendarti Tri Setyo (PT. Hafasy Dwi Nawasena, 2024)
This study examines the factors influencing the export value of Cocopeat from Indonesia to G20 member countries. The variables considered are Indonesian GDP, Importer Country GDP, Economic Distance, Exchange Rate, Indonesian Population, and Importer Country Population. The study utilizes the Gravity Model and panel data from 2017-2021 to analyze the international trade relationship of Cocopeat. The findings reveal certain patterns in Cocopeat trade from Indonesia to G20 countries. Indonesia's GDP has a positive influence on Cocopeat exports, although it is partially insignificant. On the other hand, Importer Country GDP has a significant negative effect on Cocopeat exports. Economic Distance and Exchange Rate also have a negative influence, but are not partially significant. Furthermore, the Indonesian Population shows a positive influence on Cocopeat exports, albeit not partially significant. In contrast, the Importing Country Population has a significant positive influence on Cocopeat exports from Indonesia. This research uses quantitative methods, which is a research approach that uses data in the form of numbers and statistics to measure certain variables and draw conclusions based on quantitative analysis. Data collected in quantitative research is analyzed using statistical techniques and other quantitative analysis methods. The purpose of this analysis is to identify patterns, relationships, and trends that occur in the data as well as to test research hypotheses.